2018
DOI: 10.1080/15592324.2018.1467697
|View full text |Cite
|
Sign up to set email alerts
|

Core features of the hormonal status in in vitro grown potato plants

Abstract: Some time ago, potato transformants expressing Agrobacterium-derived auxin synthesis gene tms1 were generated. These tms1-transgenic plants, showing enhanced productivity, were studied for their hormonal status, turnover and responses in comparison with control plants. For this purpose, contents of phytohormones belonging to six different classes (auxins, cytokinins, gibberellins, abscisic, jasmonic and salicylic acids) were determined by a sensitive UPLC-MS/MS method in tubers and shoots of in vitro grown pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 31 publications
(36 reference statements)
5
8
0
Order By: Relevance
“…Our results for endogenous IAA content (82.0 pmol/gFW in shoots and 62.3 pmol/gFW in roots) were similar to others reported for in vitro grown potato 27,31,33 but considerably lower than those found in greenhouse-grown plants 24 . It has been reported that the IAA content of in vitro grown shoots of the potato cultivar Miranda amounted to 81 pmol/gFW 27 .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our results for endogenous IAA content (82.0 pmol/gFW in shoots and 62.3 pmol/gFW in roots) were similar to others reported for in vitro grown potato 27,31,33 but considerably lower than those found in greenhouse-grown plants 24 . It has been reported that the IAA content of in vitro grown shoots of the potato cultivar Miranda amounted to 81 pmol/gFW 27 .…”
Section: Discussionsupporting
confidence: 91%
“…The most abundant CK nucleobase in the shoots in our study was iP, while in the roots it was tZ. iP was previously shown to be the most abundant CK nucleobase in potato shoots 32,33 . It has been shown that the biological activity of iP is important for physiological processes in plant shoots 43 .…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…All StHKs demonstrated high affinity for trans -zeatin, with similar K d at the nanomolar level (Table 3). The determined K d values were close to the values of analogous constants for CK receptors of other species (Lomin et al ., 2012, 2015, Kuderová et al ., 2015) and were well correlated with concentrations of active CKs in planta (Hirose et al ., 2008) including potato (Kolachevskaya et al ., 2017, 2018).…”
Section: Resultsmentioning
confidence: 99%